HUBUNGAN PENEMPATAN DENGAN KEPUASAN KERJA PEGAWAI DI DINAS PENDIDIKAN KABUPATEN PASAMAN BARAT - Khairo Fauzia Rahma; Nellitawati; Syahril; Lusi Susanti (CV. ADIBA AISHA AMIRA, 2024)
The background of this research is based on observations and discussions between the author and the author's employees at the West Pasaman district education office which shows low employee satisfaction. The main aim of the research is to obtain information regarding placement and job satisfaction of employees at the West Pasaman Regency Education Office, as well as assessing the significance of the relationship between employee placement and employee job satisfaction. This research uses a correlational approach to investigate the relationship between variables. The population studied involved 70 employees, with 39 of them selected as samples using proportional stratified random sampling techniques based on the Cochran formula. The instrument used is a questionnaire with a Likert scale which has been tested for validity and reliability. The main findings include: 1) Employee Job Satisfaction at the West Pasaman Regency Education Office was rated high with a score of 4.13. 2) Employee placement at the West Pasaman Regency Education Service was rated as appropriate with a score of 3.89. 3) There is a significant relationship between Employee Job Satisfaction and Employee Placement in the West Pasaman Regency Education Office with a significance level of 5%, shown by a correlation coefficient of 0.544 and a correlation significance test of 3.941.